Enhanced resistance of Trichoderma harzianum LZDX-32-08 to hygromycin B induced by sea salt - Yu, Xijia; Wei, Huiling; Liu, Xianrui; Liu, Dong; Fan, Aili; Su, Haijia (Biotechnology letters, 2021)
Objectives To determine the effect of sea salt on the resistance of Trichoderma harzianum LZDX-32-08 to hygromycin B and speculate the possible mechanisms involved via transcriptome analysis. Results Sea salt addition in media to simulate marine environment significantly increased the tolerance of marine-derived fungus Trichoderma harzianum LZDX-32-08 to hygromycin B from 40 to 500 μg/ml. Meanwhile, sea salt addition also elicited the hygromycin B resistance of 5 other marine or terrestrial fungi. Transcriptomic analyses of T. harzianum cultivated on PDA, PDA supplemented with sea salt and PDA with both sea salt and hygromycin B revealed that genes coding for P-type ATPases, multidrug resistance related transporters and acetyltransferases were up-regulated, while genes coding for Ca 2+ /H + antiporter and 1,3-glucosidase were down-regulated, indicating probable increased efflux and inactivation of hygromycin B as well as enhanced biofilm formation, which could jointly contribute to the drug resistance. Conclusions Marine environment or high ion concentration in the environment could be an importance inducer for antifungal resistance. Possible mechanisms and related key genes were proposed for understanding the molecular basis and overcoming this resistance.